PELAPORAN KERUGIAN PENURUNAN NILAI GOODWILL SERTA DAMPAKNYA TERHADAP NILAI PERUSAHAAN - Nuryani, Nunung; Samsudiono, Ilham (Program Studi Akuntansi FPEB UPI, 2014)
This study objective is to examine the determinants of the firm’s tendency to report goodwill impairment losses and it’s impact on the value of the firms. The agency theory states that managers may take some advantages of information asymmetry and utilize the accounting methods choice for private motives. Consistent with the theory, the new accounting standard for goodwill has given some flexibilities to managers to act opportunistic. On the other hand, the signaling theory explains that goodwill impairment losses is considered as bad news by investors because it relates to the decrease of the firm’s ability to generate cash inflow in the future, that will ultimately affect the value of the firm.We find that the reporting incentive (income smoothing), firm performance, `and auditor quality affects the firm’s tendency to report goodwill impairment loss, while the debt covenant does not affect the firm’s tendency to report goodwill impairment loss. We also find that reported goodwill impairment loss affects the firm’s value.